The Role of Telemedicine Technology in Improving Access to Health Services in Remote Areas - Rizki Perdana, Muhammad (Journal of Health, Medicine and Nursing, 2024)
This study explores the role of telemedicine technology in improving access to health services in remote areas. With a focus on the implementation of telemedicine in the context of public health, this study analyzes how the use of digital platforms can reduce geographical barriers and improve the quality of health services. The research method used is surveys and in-depth interviews with health workers and patients in remote areas. The results show that telemedicine significantly improves accessibility, speeds up response time to medical needs, and increases patient involvement in the treatment process. In addition, challenges such as internet infrastructure and digital literacy still need to be overcome to optimize the application of this technology. This study recommends strengthening policies and investments in telemedicine infrastructure to support the improvement of health services in underserved areas.